Widespread changes in UK air quality observed from space. (14th June 2018) - Pope, Richard J.; Arnold, Stephen R.; Chipperfield, Martyn P.; Latter, Barry G.; Siddans, Richard; Kerridge, Brian J.
Abstract : Previous studies have used surface observations of pollutants (e.g., nitrogen dioxide [NO2 ] and aerosols) to evaluate improvements in United Kingdom (UK) air quality over recent decades. However, surface monitoring networks provide limited spatial coverage and are not always representative of air quality over a wider region. Satellite observations, such as tropospheric column NO2 (TCNO2 ), aerosol optical depth (AOD) and sub‐column (0–6 km) ozone (SCO3 ), provide widespread monitoring of air quality on a national scale. In this study, we use such observations to analyse trends in UK air quality, between 2005 and 2015, finding significant decreases in TCNO2 and AOD over UK pollution hotspots. The largest changes in short‐lived NO2 are located over populated (i.e., source) regions, associated with large emissions of nitrogen oxides (NO x ). AOD changes are more spread out, and less strongly associated with source regions, due to a longer aerosol lifetime, secondary aerosol formation and non‐urban aerosol sources. SCO3 shows no significant trends over England/Wales, but significant positive trends over Scotland, which is consistent with previous studies of changes in background tropospheric ozone in other remote regions of north‐western Europe. Abstract : Satellite observations, such as tropospheric column NO2 (TCNO2 ) shown in the figure, provide widespread monitoring of air quality on a national scale. Investigated observational trends in UK air quality, between 2005 and 2015, showed significant decrease in TCNO2 and aerosol optical depth (AOD) over the urban regions (e.g., London). This is a result of government and European Union (EU) legislation. Trends in sub‐column (0–6 km) ozone (SCO3 ) were insignificant over England/Wales, but significantly positive over Scotland. Ozone monitoring instrument (OMI) tropospheric column NO2 (10 15  molecules/cm 2 ) for the United Kingdom between 2005 and 2015.